Pengenalan Aplikasi Bisnis Online Dalam Upaya Peningkatan Literasi Teknologi dan Pengembangan Usaha Digital Bagi Pensiunan di Kota Bandung - Dewi Kumalasari, Amalina; Saragih, Rohmat; Anita Silvianita; Arthadita, Sherly; Rubianti, Nurafni; Nur Hasanah, Yulia; Akbar, Aldi; Nur Utami8, Fitriani (ISAS (Indonesian Society of Applied Science), 2024)
Setting up a business can be an option for someone to work after retirement, and technological developments can accelerate business development, especially small businesses, to enable them to reach a wider market at relatively low costs. Technology is very closely related to people's daily lives. However, older people often have limitations in learning new technologies. Therefore, technological literacy is very important nowadays, so developing technology can be used effectively and positively impact users. As a university that has a vision of playing an active role in the development of technology, science, and arts based on technology, the Faculty of Communication and Business, Telkom University plays an active role in this progress, one of which is through contributions in increasing technological literacy for business people. The introduction of online business applications for retirees who own small businesses in Bandung is a form of community service aimed at increasing the adoption of technology and skills to develop online businesses effectively. This activity was carried out using the seminar method and practical use of business applications. This activity was attended by 30 retirees of the Wredatama Association of the Republic of Indonesia (PWRI) West Java, who already have businesses.